2010
DOI: 10.1051/0004-6361/201014266
|View full text |Cite
|
Sign up to set email alerts
|

Absolute dimensions of eclipsing binaries

Abstract: Context. Double-lined, detached eclipsing binaries are our main source for accurate stellar masses and radii. In this paper we focus on the 1.15-1.70 M interval where convective core overshoot is gradually ramped up in theoretical evolutionary models. Aims. We aim to determine absolute dimensions and abundances for the F-type detached eclipsing binary BK Peg, and to perform a detailed comparison with results from recent stellar evolutionary models, including a sample of previously studied systems with accurate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 62 publications
6
43
1
Order By: Relevance
“…Claret 2007;Lacy et al 2008;Clausen et al 2010). Although our results do not directly allow estimation of the errors in the recovered best convective core-overshooting parameter that is consistent with the observations, we found that the bias induced by a mild convective core overshooting scenario on age estimate is about one-half of the 1σ expected error in age estimate.…”
Section: Convective Core Overshootingcontrasting
confidence: 72%
See 1 more Smart Citation
“…Claret 2007;Lacy et al 2008;Clausen et al 2010). Although our results do not directly allow estimation of the errors in the recovered best convective core-overshooting parameter that is consistent with the observations, we found that the bias induced by a mild convective core overshooting scenario on age estimate is about one-half of the 1σ expected error in age estimate.…”
Section: Convective Core Overshootingcontrasting
confidence: 72%
“…This sometimes leads to introducing and/or calibrating some physical processes in evolutionary codes, such as convective core overshooting, or to varying the external convection efficiency through the mixing-length parameter (see e.g. Andersen 1991;Pols et al 1997;Ribas et al 2000;Torres et al 2006Torres et al , 2010Torres et al , 2014Morales et al 2009;Clausen et al 2009Clausen et al , 2010, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This or a similar test is often applied to binaries in order to test stellar evolution and investigate convective core overshooting (see e.g. Andersen 1991;Schroder et al 1997;Pols et al 1997;Clausen et al 2010;Torres et al 2010Torres et al , 2014, and references therein).…”
Section: Description Of Our Testmentioning
confidence: 99%
“…Stellar models succeed in predicting the mass-radius relation to an accuracy of a few percent for main-sequence stars with M M M 5  < <   (e.g., Andersen 1991). Systematic discrepancies between model and observation in the mass-radius relation for a given age have been associated with the amount of convective core overshoot by Clausen et al (2010), but these are below 1%. Low-mass stars with M M  <  are the most common stars in the solar neighborhood, but only a very limited number of these are well-characterized (Torres 2013).…”
Section: Introductionmentioning
confidence: 99%